Implementation of Co-Curricular Programs in Improving the Ability to Read the Quran - Ulpah, Ghina; Nursobah, Asep; Haryanti, Erni; Erihadiana, Mohammad; Husain, Husain; Huda, Miftahul; Razali, Nabihah Husna (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
The ability to read the Quran is a fundamental skill in religious education for students in schools. Co-curricular programs can play an important role in improving this ability. This study aims to explore the implementation of co-curricular programs in improving the ability to read the Quran in primary schools. This study used a qualitative approach with an analytical description design. Data were collected through in-depth interviews with teachers, students, and parents, as well as observation of learning activities. The research subjects consisted of 30 students who participated in the co-curricular Quran reading program for one semester. The results showed that the implementation of this co-curricular program contributed positively to the improvement of students' Quran reading skills. Teachers reported significant improvements in students' Quran reading proficiency, as shown through increased evaluation scores. In addition, parents' involvement in supporting the program was also a determining factor in the success of students' improvement. This study indicates that a well-designed co-curricular program can be an effective solution in improving Quran reading skills. The findings emphasize the importance of collaboration between teachers, students and parents in creating a supportive learning environment. Recommendations for future research include the development of a more structured program as well as a long-term evaluation of the sustainability of improving Quran reading skills.